A 3D FEM Mesoscale Numerical Analysis of Concrete Tensile Strength Behaviour. (14th July 2021) - Guo, Chao; Lu, Zhengran
Abstract : A three-dimensional (3D) finite element method (FEM) based on an inserted cohesive element numerical analysis procedure was developed for concrete mesoscale systems on the ABAQUS platform with python scripts. Aggregates were generated based on dividing the existing geometrical element algorithms to randomize arbitrary spheres. Simultaneously, randomizations of the maximum aggregate size and uniform distributions of aggregate particles were also considered. An FEM for the mortar phase in concrete mesoscale systems was generated along with the interfacial transition zone (ITZ) by inserting a cohesive element. Numerical parameter analyses were performed for nine different concrete systems by varying the coarse aggregate volume fraction ( α ) and the ITZ tension strength (ITZ-S). The mechanical performance of concrete systems with the coupling effects of α and ITZ-S was evaluated for simulated tensile loading. The results of the numerical simulations for mechanical properties, such as the simulated tensile strengths and tension damage behaviour of concrete systems, were verified with experimental results. The proposed aggregate and ITZ generation approach and numerical simulation procedure can be used by researchers to better understand how aggregate volume fraction and ITZ strength affect the tensile behaviour of concrete mesoscale systems.